Specificity switching in virus–receptor complexes - Stehle, Thilo (Curr Opin Struct Biol, 2009)
Several structures of complexes between viral attachment proteins and their cellular receptors have been determined recently, enhancing our understanding of the molecular recognition processes that guide formation of virus–receptor complexes. Moreover, these structures also highlight strategies by which highly similar viral proteins within a single virus family can adapt to engage different receptors. Consequences of such differences are altered tropism and pathogenicity. An improved understanding of the molecular details of this specificity switching in receptor binding will help to establish links between receptor tropism, spread, and disease. Moreover, it also has relevance for the design and use of viruses as gene delivery vehicles with altered properties as well as for the identification of target viral epitopes of new vaccines.